Migration of the Ukrainian Population Economic, Institutional and Sociocultural Factors - Bilan, Yuriy (Ubiquity Press, 2017)
Ukraine is a "border" society, situated culturally and socio-politically between Eurasian and Euro-Atlantic poles of attraction. The influence of these two distinct cultures can be seen throughout Ukrainian society, but particularly in its patterns of migration. In this book, Dr Hab. Y. Bilan analyses external migration from Ukraine using a system analysis approach combining econometric analysis and statistical modelling, historiographical and institutional analysis, and quantitative and qualitative sociological analysis with special attention to media discourse and congregational, demographic, gender and regional dimensions.The author's analysis builds on statistical data and a range of studies in English, Ukrainian, Russian and Polish, presenting the Ukrainian case as applicable to other border societies and beyond.
Description based on print version record.
KU Select 2016 Front List Collection
Keywords: Social Science / Sociology; Social sciences; Electronic books